Nearshore Monitoring With X‐Band Radar: Maximizing Utility in Dynamic and Complex Environments. Issue 4 (28th April 2021) - Atkinson, J.; Esteves, L. S.; Williams, J. J.; Bell, P. S.; McCann, D. L.
Abstract: Coastal management and engineering applications require data that quantify the nature and magnitude of changes in nearshore bathymetry. However, bathymetric surveys are usually infrequent due to high costs and complex logistics. This study demonstrates that ground‐based X‐band radar offers a cost‐effective means to monitor nearshore changes at relatively high frequency and over large areas. A new data quality and processing framework was developed to reduce uncertainties in the estimates of radar‐derived bathymetry and tested using data from an 18‐months installation at Thorpeness (UK). In addition to data calibration and validation, two new elements are integrated to reduce the influence of data scatter and outliers: (a) an automated selection of periods of "good data" and (b) the application of a depth‐memory stabilization. For conditions when the wave height is >1 m, the accuracy of the radar‐derived depths is shown to be ±0.5 m (95% confidence interval) at 40 × 40‐m spatial resolution. At Thorpeness, radar‐derived bathymetry changes exceeding this error were observed at time scales ranging from 3 weeks to 6 months. These data enabled quantification of changes in nearshore sediment volume at frequencies and spatial cover that would be difficult and/or expensive to obtain by other methods. It is shown that the volume of nearshore sediment movement occurring at time scale as short as few weeks are comparable with the annual longshore transport rates reported in this area. The use of radar can provide an early warning of changes in offshore bathymetry likely to impact vulnerable coastal locations. Plain Language Summary: Near the shore, waves and currents can cause natural changes in seabed elevation (due to removal or deposition of mud, sand, and gravel). On the other hand, changes in seabed elevation can alter the waves approaching the shore and influence the location and amount of coastal erosion. Measurements of these changes are required for coastal management and a wide range of engineering works. However, surveys of the seabed are usually infrequent owing to high costs and logistical difficulties. This paper analyses data from a marine radar installed on a cliff top to produce a series of seabed elevation (bathymetric) maps off the Thorpeness coast (UK). A new data quality assessment was developed to produce improved estimates of water depth. Results demonstrate that radar can offer a cost‐effective alternative to conventional surveys and enable frequent monitoring of the seabed over large areas. The use of radar in the present study enabled the measurement of changes in nearshore seabed elevation within periods as short as 3 weeks. Radar‐derived bathymetric maps can provide an early warning of seabed changes and allow more time to plan and implement responses to mitigate the impacts of coastal erosion. Key Points: Uncertainty in radar‐derived bathymetry (2.5–10‐m depths) was greatly reduced using a new data processing and quality control framework Bathymetry changes assessed for periods as short as 3 weeks were shown to be accurate to ±0.50 m at a 40 × 40‐m resolution The volume of nearshore sediment movement over a few weeks was comparable with annual longshore transport rates reported in this area